A New ‘cyclotis-morphotype’ Species of Tube-Nosed Bat (Chiroptera: Vespertilionidae: Murina) from China - Xin Mou; Yishun Qian; Wen Wang; Wenxiang Zhang; Jianjie Wang; Song Li (Animals)
During an examination of various specimens previously collected from different locations at different times, we discovered four Murina specimens that had been collected in October and December 2023 from the Huanglianshan National Nature Reserve, Lvchun, Yunnan, China. Morphologically, these specimens can be distinguished from M. pluvialis and other congeneric species based on a combination of body size, hair distribution, fur colour, and skull and teeth characteristics; molecularly, an analysis of Cyt b and COI gene sequences showed that these specimens form a monophyletic group with M. pluvialis with high posterior probability and bootstrap support values. Furthermore, the genetic distance between our specimens and M. pluvialis was greater than the minimum threshold for interspecific differentiation, indicating that they are phylogenetically close but have diverged. Based on the above assessment of morphological characteristics and molecular data analysis, these specimens were determined to represent a previously unidentified species, designated Murina lvchun Xin Mou & Song Li, sp. nov.